Politics, culture, and the legitimacy of disease: the case of Buerger's disease. Issue 9 (September 2016) - Lockwood, Stephen; Bresler, Scott; Granter, Scott
Abstract Thromboangiitis obliterans (TAO) or Buerger's disease is a rare form of vasculitis with distinctive clinical and pathological features that carries significant morbidity, often leading to amputation, and is strongly associated with tobacco smoking. Despite its distinctive clinicopathological characteristics, the existence of TAO as an entitysui generis was challenged for many years as it languished in relative obscurity. Then, as societal attitudes towards smoking changed, TAO not only became accepted as a disease entity, it quite literally became a poster child to illustrate the ills of smoking. Herein, we examine the history of TAO to illustrate the power of societal attitudes and politics in shaping medicine.